Development of baamboozle-based learning media on Pancasila and Civics subjects in class V - Cahaya Auzi; Sri Yunita; Sugiharto Sugiharto (Inovasi Kurikulum, 2025)
This study aims to produce a product in the form of interactive learning media based on baamboozle in the subject of PPKn. This research is development research using the ADDIE model. This baamboozle-based interactive learning media was developed and then tested for feasibility by material experts, media experts, and linguists, followed by an effectiveness and a practicality test. The results of the feasibility test obtained an average percentage of assessment by material experts of 91 percent, media experts 92 percent, and linguists 77 percent. The practicality of the media was measured using a questionnaire and obtained a score of 93.75 in the very practical category. The effectiveness of the media was obtained from student learning outcomes through the calculation of N-Gain with an average of 0.71 placing the average in the highest effectiveness category, the acquisition of student scores after using baamboozle based interactive learning media is in category very good with an average percentage of 89.15 and the results of the N-Gain calculation with an average of 0.75. It is concluded that baamboozle-based interactive learning media on PPKn are declared feasible, practical, and effective to use as learning media.   Abstrak Penelitian ini bertujuan untuk menghasilkan produk berupa media pembelajaran interaktif berbasis baamboozle pada mata pelajaran PPKn. Penelitian ini merupakan penelitian pengembangan dengan menggunakan model ADDIE. Media pembelajaran interaktif berbasis baamboozle ini dikembangkan kemudian diuji kelayakannya oleh ahli materi, ahli media dan ahli bahasa, dilanjutkan dengan uji keefektifan dan uji kepraktisan. Hasil uji kelayakan diperoleh persentase rata-rata penilaian oleh ahli materi sebesar 91 persen, ahli media 92 persen, dan ahli bahasa 72 persen. Kepraktisan media diukur dengan menggunakan angket dan memperoleh skor 93.75 dengan kategori sangat praktis. Keefektifan media diperoleh dari hasil belajar peserta didik melalui perhitungan N-Gain dengan rata-rata 0.71 menempatkan rata-rata tersebut pada kategori keefektifan paling tinggi, perolehan nilai peserta didik setelah menggunakan media pembelajaran interaktif berbasis baamboozle berada pada kategori sangat baik dengan persentase rata-rata 89.15 dan hasil perhitungan N-Gain dengan rata-rata 0.75. Disimpulkan bahwa media pembelajaran interaktif berbasis baambozlee pada mata pelajaran PPKn dinyatakan layak, praktis, dan efektif digunakan sebagai media pembelajaran. Kata Kunci: ADDIE; baamboozle; multimedia interaktif; pendidikan Pancasila dan kewarganegaraan